2019
DOI: 10.1002/ccr3.2453
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of a patient with spinal cord decompression sickness: First case report from Saudi Arabia

Abstract: This case brings attention to development of rehabilitation protocols for patients with decompression sickness (DCS). A lack of data regarding DCS renders the need of conducting multicenter studies to document the epidemiology and outcomes of spinal cord DCS in Saudi Arabia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Previously, studies showed the impact of post-decompression surgery complications on reducing BMI in the Saudi population (Aleissa et al, 2022;Ullah et al, 2019). Not many studies have studied the occurrence of this complication particularly in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, studies showed the impact of post-decompression surgery complications on reducing BMI in the Saudi population (Aleissa et al, 2022;Ullah et al, 2019). Not many studies have studied the occurrence of this complication particularly in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%